Analysis Of Online Learning Difficulties In Fifth Grade Students Of SD Negeri 0701 Rotan Sogo - Netty Herawati Hasibuan (STKIP Rokania Pasir Pangaraian, 2022)
The purpose of this study was to identify the factors that affect the learning difficulties of fifth grade students with access to topical materials through online learning activities and the factors that affect the fifth grade students' learning difficulties with access to topical materials through online learning activities. This type of research is descriptive qualitative research. In this study, researchers analyzed the learning difficulties experienced by students when participating in online learning activities. Therefore, researchers used descriptive methods and used qualitative research types. Because the research produces data in written or oral form from the observed students as well as resource staff (ie classroom teachers). The results of this study indicate that the factors that influence the difficulty of learning the subject matter of class V students through online learning activities are internal factors and external factors that exist in students. Such as student interest in learning factors, student learning motivation factors, parental support factors, family economic factors, playmates factors, intelligence factors, etc. The most important learning difficulty factor occurred in five classes of students who studied topic material through online learning activities, namely student interest in learning with an average of 13.24